Is the taxonomy of Brachycephalus (Anura: Brachycephalidae) in need of rescue? A reply to Condez et al. (2017) - Pie, Marcio R.; Ribeiro, Luiz F.; Bornschein, Marcos R. (Zootaxa, 2017)
Brachycephalus is a fascinating genus of miniaturized frogs endemic to the Brazilian Atlantic Forest (Bornschein et al. 2016a). Given the many new species that have been recently discovered (20 species over the past 10 years [Frost 2017]) and their often microendemic distribution (see Bornschein et al. 2016a), there has been an increasing awareness about the need for more extensive field work to locate additional new species, to describe their geographical distributions, and to devise comprehensive efforts to ensure their conservation. In a recent correspondence in Zootaxa, Condez et al. (2017) singled out nine of those new species that have been described by our research group (Ribeiro et al. 2015; Pie & Ribeiro 2015; Bornschein et al. 2016b); two additional species (Ribeiro et al. 2017) were described after their paper was published. According to Condez et al. (2017), our species descriptions included “inadequate diagnoses, which lacked indispensable information for any further comparisons among species” (p. 395). Herein, we explore the extent to which their arguments would undermine the validity of those species.